Hydatidiform mole: age‐related clinical presentation and high rate of severe complications in older women. (20th March 2014) - Mangili, Giorgia; Giorgione, Veronica; Gentile, Cinzia; Bergamini, Alice; Pella, Francesca; Almirante, Giada; Candiani, Massimo
Abstract Objective The purpose of this study was to demonstrate differences in clinical presentation of hydatidiform mole between women ≥40 years and younger women. Design Retrospective study. Setting A tertiary referral unit in northern Italy. Population Three hundred and sixty‐five women with hydatidiform mole were divided into group A (<40 years, 318 cases) and group B (≥40 years, 47 cases). Methods Clinical presentation between groups A and B was analyzed, also considering partial hydatidiform mole and complete hydatidiform mole. Main outcome measures Differences in clinical presentation according to woman's age. Results In group B the diagnosis of hydatidiform mole at ≥12 gestational weeks was more frequent (p < 0.001) and the detection of ultrasound features was higher (p < 0.05) than in group A. Vaginal bleeding (p < 0.05), increased uterine volume (p < 0.0001) and hyperemesis (p < 0.05) occurred more frequently in group B. In the women with complete hydatidiform mole, group B women presented with vaginal bleeding (p < 0.001), increased uterine volume (p < 0.05) and hyperemesis (p < 0.05) more frequently than group A women. Complete hydatidiform mole was more commonly diagnosed after 12 weeks of gestation in group B (p < 0.0001). In women ≥50 years, an increased rate of disease‐related complications was detected. Conclusions The clinical features of hydatidiform mole in women ≥40 years are different from those seen in younger women. Failures in the early detection of hydatidiform mole in older women may expose them to a higher rate of severe complications.